2019
DOI: 10.1039/c8nj06249h
|View full text |Cite
|
Sign up to set email alerts
|

Toxic organic solvent adsorption by a hydrophobic covalent polymer

Abstract: A hydrophobic needle-shaped novel covalent polymer has been synthesized at ambient temperature for adsorption of toxic organics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The chemical stability of the as-synthesized CPCMERI-2 has been checked, as reported in our previous work. 36 The material displays good chemical stability in 2 N HCl, 8 N NaOH and even in Lewis acid-containing aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical stability of the as-synthesized CPCMERI-2 has been checked, as reported in our previous work. 36 The material displays good chemical stability in 2 N HCl, 8 N NaOH and even in Lewis acid-containing aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, metal–organic frameworks (MOFs), covalent–organic frameworks (COFs), and hydrogen-bonded organic frameworks (HOFs) have been investigated. Among these materials, MOFs, a new class of functional material constructed by rigid organic linkers and metal ions/metal clusters, were considered as the promising candidates for Xe and Kr separation due to their high surface area, tailorable pore structures, and versatile functionalities. MOFs were used in different fields such as ion-exchange, photonics, sensors, and especially gas storage and separation. Until now, several MOFs were studied as adsorbents for Xe/Kr separation in both experimental and computational aspects. Thallapally and co-workers synthesized a microporous MOF (SBMOF-2) to separate Xe and Kr . Wang et al reported a 3D thorium MOF (SCU-11) which exhibited a unique 10-coordinate geometry for metal ion of Th 4+ , resulting in superior Xe/Kr uptake and separation .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are highly crystalline materials. Inorganic units (metal ions or metal clusters) and organic ligands bond through covalent or coordinate bonds to form MOFs. Recently, MOFs have attained much consideration because of their remarkable surface area, high thermal stability, and large pore volume. Research on MOFs has attracted much attention due to their diverse and tunable porosities . The selection of metal ions, linkers, solvents, and synthetic procedures tunes the MOF with controlled size and shape .…”
Section: Introductionmentioning
confidence: 99%
“…The selection of metal ions, linkers, solvents, and synthetic procedures tunes the MOF with controlled size and shape . MOFs have been widely applied in catalysis, energy and gas storage, drug delivery, adsorption, and sensors. However, their solubility, chemical stability, and electrical conductivity significantly hamper the full potential of MOFs. MOFs synthesized by the solvothermal method with diverse morphology cannot meet the requirements of a good electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%